An Analytical Approach to Understand Customer Relationship Management in Indian Banking Sector from the Perspective of Customers - Bansal, Dr. Sanjeev; Malik, Dr. Garima (Ushus Journal of Business Management, 2015)
In recent years, significant developments have been experienced in the banking sector. With the improved technology, banks have become institutions that offer services for 24 hours through telephone, internet and ATMs. Besides the classic banking services, they have taken over a number of activities such as automatic billing, which facilitate the lives of the customers. To maximize lifetime profitability from valued customers, banks have changed traditional silo mindset and have adopted Customer Relationship Management (CRM) techniques.This paper examines the relationship between thecustomer loyalty and CRM in National Capital Region of India. Methodology of the paper has been designed such that, it abstracts the scales into 5 dimensions related to CRM of banks. This paper uses regression analysis to arrive at a model which explains customer loyalty. This paper also provides insights for the banks which adopt CRM at a strategic standpoint as well as operational standpoint and implement a customer–centric vision.